Differentiating Bipolar Disorder–Not Otherwise Specified and Severe Mood Dysregulation - Towbin, Kenneth (2013)
OBJECTIVE: Bipolar Disorder–Not Otherwise Specified (BP-NOS) and Severe Mood Dysregulation (SMD) are severe mood disorders that were both defined to address questions about the diagnosis of bipolar disorder (BD) in youth. SMD and BP-NOS are distinct phenotypes that differ in clinical presentation and longitudinal course. The purpose of this review is to inform clinicians about the clinical features of the two phenotypes and about the research literature distinguishing them. METHOD: We review the literature on SMD as studied in the National Institute of Mental Health Intramural Research Program and on BP-NOS in youth. For BP-NOS, we focus on the phenotype defined in the Course of Bipolar Youth (COBY) study, since this has received the most study. RESULTS: SMD is characterized by impairing, chronic irritability without distinct manic episodes. Most commonly, BP-NOS is characterized by manic, mixed or hypomanic episodes that are too short to meet DSM-IV-TR duration criterion. Research provides strong, albeit suggestive, evidence that SMD is not a form of BD; the most convincing evidence are longitudinal data indicating that youth with SMD are not at high risk to develop BD as they age. The BP-NOS phenotype appears to be on a diagnostic continuum with BD type I and type II. BP-NOS and BD- type I subjects have similar symptom and family history profiles, and youth with BP-NOS are at high risk to develop BD as they age. Currently, little research guides treatment for either phenotype. CONCLUSIONS: Pressing research needs include identifying effective treatments for these phenotypes, ascertaining biomarkers that predict conversion from BP-NOS to BD, elucidating associations between SMD and other disorders, and defining the neural circuitry mediating each condition.